2018
DOI: 10.1299/jamdsm.2018jamdsm0016
|View full text |Cite
|
Sign up to set email alerts
|

Potential of oil-lubricated cylindrical plastic gears

Abstract: Bending strength of injection molded polyacetal test gears is investigated in back-to-back testing using oillubrication. To validate state of the art calculation methods, tooth geometries with a variable number of teeth are investigated, maintaining a constant center distance and transmission ratio. To enable testing on a constant level of tooth temperature for variable torque loads and speeds, occurring tooth temperatures are measured and considered in latter testing. Test results show that bending strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Highly-stressed machine elements making of thermoplastics are often lubricated to dissipate frictional losses, while at the same time reducing friction and wear. As a result of this, a significant increase in the transmittable power can be achieved, as exemplarily shown by Hasl et al [3] and Illenberger et al [4] for polymer gears.…”
Section: Introductionmentioning
confidence: 71%
“…Highly-stressed machine elements making of thermoplastics are often lubricated to dissipate frictional losses, while at the same time reducing friction and wear. As a result of this, a significant increase in the transmittable power can be achieved, as exemplarily shown by Hasl et al [3] and Illenberger et al [4] for polymer gears.…”
Section: Introductionmentioning
confidence: 71%
“…Abrasive wear of the tooth flanks leads to a continuous reduction of the tooth crosssection and thus limits the lifetime. Due to the reduction in wear, fatigue damages such as tooth root breakage and pitting are increasingly emerging in oil-lubricated operation and extended running times [10,11]. For the calculation of the tooth root load capacity and the tooth flank load capacity, VDI 2736 [2] provides calculation approaches that are strongly based on the principles according to DIN 3990 [12] for metallic gears.…”
mentioning
confidence: 99%
“…25,27 Estimation of bending stress without considering the effect of deflection-induced load sharing can result in unrealistically high bending stress values. Experimental results of Hasl et al 16 revealed that the load-carrying capacity of POM gears was significantly higher than the predicted values, as the effect of the increased contact ratio was disregarded by the VDI 2736 method. In asymmetric polymer gears, deflection-induced load sharing improves the bending fatigue life when the drive side pressure angle is lower than the coast side.…”
Section: Bending Stress and Load Sharing In Polymer Gearsmentioning
confidence: 93%
“…Nonetheless, the evaluation of bending fatigue strength is essential since tooth breakage due to bending fatigue occurs in polymer gears. [14][15][16] The polymer gear design must incorporate an asymmetric tooth form, optimized fillet profile, and transitional contact ratio to achieve a robust bending fatigue strength. 1 An asymmetric gear tooth consists of different pressure angles on either side of the tooth.…”
Section: Introductionmentioning
confidence: 99%